Siklus hidup dan kesintasan ulat grayak Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) dari beberapa daerah di Jawa Barat: Life cycle and survivorship rate of fall armyworm Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) from several areas in West Java - Susanto, Agus; Leider, Putri Artha; Maharani, Yani; Rizkie, Lilian; Bari, Ichsan Nurul; Subakti-Putri, Syifa Nabilah (Perhimpunan Entomologi Indonesia, 2024)
Spodoptera frugiperda Smith is a major pest of corn plants. Information on the life cycle and survival of this pest is important for proper and effective control. This study was conducted to determine the life cycle and survival of S. frugiperda in several areas in West Java. This study was conducted from June to August 2020. Samples were taken from several areas divided into three categories: highlands in Lembang District (1,100 m asl), middlelands in Jatinangor District (858 m asl), and the lowlands in Tarikolot District (103 m asl). Sampling used the observation method to study the effect of differences in altitude on population, life cycle, and survival. The results showed that there was no significant difference in the development time of S. frugiperda among the three different areas. The average development time of S. fugiperda was 24.55 days (highlands), 24.36 days (middlelands), and 24.07 days (lowlands). The survival percentage of S. frugiperda from highland, middle, and lowland areas in the egg phase was 95.44%, 97.34%, and 96.89%, larval phase 98.46%, 98.65%, and 98.48%, and pupal phase 87.63%, 88.08%, and 93.43%. The sex ratio of S. frugiperda from the highlands was 1:1, from the middlelands was 1:1.28, and from the lowlands was 1:0.89. Location did not affect the width parameter of the head capsule in S. frugiperda. Based on the test results, it is known that the life cycle, survival, and sex ratio of S. frugiperda from several regions do not have significant differences.